PENGARUH BRAND IMAGE, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK IPHONE DI JABODETABEK - Muhammad Romadhoni Rizki Hidayanto (2023)
One of the most popular smartphone brands sold in Indonesia is the iPhone. This quantitative research aims to determine the effect of brand image, product quality, and price on purchasing decisions for iPhone products. This study uses non-probability sampling techniques with purposive sampling. The research sample is iPhone users who live in Jabodetabek, and are in the age range of 17-42 years. Data was collected by distributing questionnaires to 100 respondents. Data analysis through descriptive and inferential analysis using Partial Least Square with the SmartPLS 4.0 test tool. From the results of the study it was found that (1) brand image has a positive and significant influence on purchasing decisions with a path coefficient of 0.331. (2) Product quality has a positive and significant influence on purchasing decisions with a path coefficient of 0.467. (3) Price has no effect and is not significant to purchasing decisions. The variables used in this study such as brand image, product quality, and price have an influence on the purchasing decision variable by 57.5% and the remaining 42.5% is influenced by other variables not used in this study.